Design of Lecturer and Student Absence System Based on SMS Gateway - Tri Cicik Wijayanti; Herra Herryani; Arifannisa Arifannisa; Liswandi Liswandi; Nanda Saputra (International Journal of Artificial Intelligence Research, 2022)
The presence of lecturers and students is one factor that influences the quality of teaching and learning activities. Processing information on the company of lecturers and students manually by providing information on the presence of student lecturers in the attendance book. To overcome this problem, this Belitian pen automatically processes lecturer and student information on the presence of lecturers and students by using an SMS Gateway. In general, incoming Short Message Service will be read because of the nature of cellphones, which are private property, and psychologically, someone wants always to be considered necessary. So whatever type of Short Message Service comes in, that person will open and read it. Messages can be conveyed quickly and more effectively without leaflets or notices that are not necessarily read. In addition to sending messages between cell phone users, the Short Message Service is suitable for interacting with a computer-based information system. To obtain accurate data in every job, where the technology is increasingly modern, from the analysis, the researchers carried out the Student Attendance Information System in a system that can increase work efficiency and effectiveness. This research has stages as follows analyzing the needs of lecturers, academics, and students, developing system designs and SMS codes, designing databases, creating systems, testing systems, and determining whether the system is accepted and implemented on campus. This research results from an information system based on SMS Gateway, including student attendance, where the system automatically sends SMS to parents.